تضمين التعلم الخدمي ومشروعاته في كتب التربية المدنية لمرحلة التعليم المتوسط - عتروس، نبيل (جامعة عنابة, 2017)
The study aimed to identify the most important Service-Learning projects that should be available in the books of civic education for middle school level, and to identify these projects actually contained in these books. As a study approach, the content analysis method of the four Civic Education Textbooks to the middle school level for the 2013/2014 academic year was used. The study ended up with the construction of the Service Learning projects list that should be available in those books which contained (31) projects. It was found that, after the analysis of these books, the projects aiming to development are deficient, as there is no clear plan in terms of preparation, planning and implementation.
هدفت الدراسة إلى تحديد أهم مشروعات التعلم الخدمي الواجب توافرها في كتب التربية المدنية لمرحلة التعليم المتوسط، والتعرف على تلك المشروعات المتضمنة فعليا في تلك الكتب. استخدم في منهج الدراسة أسلوب تحليل المحتوى لكتب التربية المدنية الأربعة لمرحلة التعليم المتوسط للعام الدراسي 2013/ 2014. أسفرت نتائج الدراسة على بناء قائمة بمشروعات التعلم الخدمي الواجب توافرها في تلك الكتب احتوت واحدا وثلاثين (31) مشروعا. تبين بعد تحليل تلك الكتب قلة المشاريع الهادفة إلى التطوير، وافتقارها إلى خطة واضحة المعالم من حيث الإعداد والتخطيط والتنفيذ.
Keywords: التعلم الخدمي -- مشروعات التعلم الخدمي -- المواطنة -- التربیة المدنیة -- التعلیم المتوسط